Vinculação do trabalhador ao SUS no âmbito municipal: perspectivas de valorização baseadas na educação permanente em saúde - Alves, Josenildo de Sousa (2010)
The qualitative approach study about worker linkage for the Sistema Único de Saúde (SUS) and the process of Health Permanent Education (Educação Permanente em Saúde – EPS), researching a municipal system health of Bahia state, Brazil, the objective of this essay is to analyze the process of worker linkage for SUS regarding the working conditions and their participation in the construction of a management health proposal to discuss the EPS as a valorization strategy and development of the workers that integrate the local SUS. It has theoretical presupposition the workers of the municipal SUS need training for the performance of actions focused on the new sanitary practices, besides the workers’ linkage and permanency difficulty in the different places by elusiveness in great part of the municipalities of a policy focused on a linkage, valorization, qualification and participation of the worker in the SUS management. The methodological trajectory was based on the actual historical-social. The subjects of the study were 14 people: Group I (managers – definite the politics of GT = 4 people); Group II (health workers – that work in health strategy of family (ESF) = 5 people) and Group III (Key informers = 5 people). The techniques of data collecting were semi-structured interviews and documental analysis. The results show that there are several ways of worker linkage to the municipal SUS and, in EFS, the adopted worker linkage follows the working regime by consolidation of working laws (Consolidação das Leis Trabalhistas – CLT) that, despite being considered attractive it does not guarantee the workers’ stability in their working posts and; EPS revealed as a potency to be explored in the worker valorization of the SUS, well as a qualification device of their work being able to be the counterpoint to qualify the management care. Finally, this study shows as challenge the construction of effective bonds of different subjects that everyday work at SUS, in order that these workers are part of an integrated, state and universal system.